Comparative advantage in the knowledge economy : a national and organizational resource - Bhattacharyya, Rajib (Emerald Publishing Limited, 2021)
Globalization and information and communications technology (ICT) have played a pivotal role in revolutionizing value creation through the development of human capital formation. The constantly changing needs and structure of the labour market are primarily responsible for the conversion of a traditional economy relying fundamentally on the application of physical abilities to a knowledge-based economy relying on ideas, technologies and innovations. In this economy, knowledge has to be created, acquired, developed, transmitted, preserved and utilized for the improvement of individual and social welfare. Comparative Advantage in the Knowledge Economy: A National and Organizational Resource provides a comprehensive and insightful understanding of all the dimensions of a transition from a traditional to a knowledge economy. It attempts to explain how educational achievement, skilled manpower, investment in knowledge capital and analytics will be the key to success of a nation's comparative advantage in the globalized era. The volume should be of interest to students, researchers and teachers of economics, policy makers and advanced graduate students with an interest in economic analyses and development policy.
Includes index.
Keywords: Knowledge economy.; Comparative advantage (International trade); Business & Economics -- Knowledge Capital.; Economic theory & philosophy.; elektronické knihy; electronic books